2019
DOI: 10.2139/ssrn.3373720
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Effects of Residential Energy Efficiency Improvements: Evidence from Ukraine

Abstract: Untapped improvements in energy efficiency in the residential sector may deliver large savings in energy use and the CO2 associated emissions. Yet empirical assessments have been difficult and controversial. We collect monthly natural gas meter readings from a sample of homes in Transcarpathia, in Western Ukraine, an early adopter of the country's trend away from district heating, from January 2013 to April 2017, a period over which the residential natural gas tariffs rose by over 700%. We combine the monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…And 3) The free market provides the easiest access to capital markets through a direct quotation procedure for any company, whatever the size (from micro-cap to medium-sized international companies) searching to access capital markets (free from the Euronext's eligibility criteria and information disclosure requirements). This market targets primarily sophisticated or professional investors; 6 Euronext classifies firms into the 10 following sectors: basic materials; consumer goods; consumer services; financials; health care; industrials; oil & gas; technology; telecoms; utilities; 7 This dummy variable equals to 1 when the firm was more than one time named in sanction reports as victim of market manipulators; 8 This dummy variable equals to 1 when the firm was both a market manipulator and a victim for different sanction procedures; 9 This dummy variable equals to 1 when several victims were named in a given sanction report; 10 This table reports the cumulative abnormal returns (CAR ) from one day preceding the event to one day following the event (t = 0 for the Enforcement Committee and the sanction decision) and their significance levels at 5% and 10%. The abnormal returns (AR ) are computed given the augmented market model parameters, which are estimated with OLS with White-corrected standard errors over the period [-120;-11] This table reports the cumulative average abnormal returns (CAAR ) from the day preceding the event up to a specified day t in event time for the last two main steps of the sanction procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And 3) The free market provides the easiest access to capital markets through a direct quotation procedure for any company, whatever the size (from micro-cap to medium-sized international companies) searching to access capital markets (free from the Euronext's eligibility criteria and information disclosure requirements). This market targets primarily sophisticated or professional investors; 6 Euronext classifies firms into the 10 following sectors: basic materials; consumer goods; consumer services; financials; health care; industrials; oil & gas; technology; telecoms; utilities; 7 This dummy variable equals to 1 when the firm was more than one time named in sanction reports as victim of market manipulators; 8 This dummy variable equals to 1 when the firm was both a market manipulator and a victim for different sanction procedures; 9 This dummy variable equals to 1 when several victims were named in a given sanction report; 10 This table reports the cumulative abnormal returns (CAR ) from one day preceding the event to one day following the event (t = 0 for the Enforcement Committee and the sanction decision) and their significance levels at 5% and 10%. The abnormal returns (AR ) are computed given the augmented market model parameters, which are estimated with OLS with White-corrected standard errors over the period [-120;-11] This table reports the cumulative average abnormal returns (CAAR ) from the day preceding the event up to a specified day t in event time for the last two main steps of the sanction procedure.…”
Section: Resultsmentioning
confidence: 99%
“…1) Warning or blame, depending on the seriousness of the wrongdoing(s); and 2) "ban on activity", covering temporary or permanent ban on providing some or all services, suspension or withdrawal of professional license, and temporary or permanent ban on conducting some or all businesses. the EC AMF and most frequently published (possibly at least partially anonymized) by the AMF, 9 the market manipulator (firm and/or individual) and/or the AMF Chairman of the Board can appeal the decision towards four different jurisdictions: State Council, Court of Appeal of Paris, Court of Cassation, and via priority preliminary ruling on constitutionality. Sanctions were frequently appealed over the period under review (45%), with a limited success (79% of the appeals were rejected to date).…”
Section: Enforcement Of Financial Laws In Francementioning
confidence: 99%
“…Several studies reported multiple effect size estimates using slightly different models; here we chose the one with the lowest assessed risk of bias or most similar to other studies. If a study included different analyses with overlapping samples (Alberini et al, 2019;, we chose the one with the lowest risk of bias.…”
Section: Criteria For Determination Of Independent Findingsmentioning
confidence: 99%
“…in combination with the World Bank (Costolanski et al, 2013). In three other studies the interventions were funded through a combination of private and government funding (Alberini et al, 2016(Alberini et al, , 2019Hamilton et al, 2016). For example, in Alberini 4) and some were subsidised.…”
Section: Intervention Funding Mechanisms and Context Featuresmentioning
confidence: 99%
“…8 Robustness check using data prior to 2012 and direct definition of parental leave provide almost identical results as the analysis using the adapted definition of childcare leave. 9 In 2011 there was a significant change in the system of occupational classification used in the Czech Labor Force Survey. Prior to this year information on occupations was recorded using a Czech system of occupational classification, KZAM, while in 2011 the Czech Statistical Office officially started to code occupations according to ISCO.…”
Section: Datamentioning
confidence: 99%